An Awkward Fit: Antimicrobial Resistance and the Evolution of International Health Politics (1945-2022). (2022) - Kirchhelle, Claas; Podolsky, Scott H.
Abstract: Despite being acknowledged as a major global health challenge, growing levels of antimicrobial resistance (AMR) in pathogenic and commensal organisms have proven an awkward fit for international health frameworks. This article surveys the history of attempts to coordinate international responses to AMR alongside the origins and evolution of the current international health regulations (IHR). It argues that AMR, which encompasses a vast range of microbial properties and ecological reservoirs, is an awkward fit for the 'organismal' philosophies that centre on the rapid control of individual pathogens that have characterised international policy-making since the 19th century.